The Role of Adjacency Pairs to Create Politeness Strategies in Students’ Phatic Utterances - Ratna Padmi Trihartanti; Seldie Julyana Septian (Register Journal, 2021)
Adjacency pair is one of the language features to make utterances more polite as it creates turn-taking, which means that none of the participants dominates. Adjacency pairs also create functions of phatic communication as stated by Padilla Cruz. According to Levinson, there are nine patterns of adjacency pairs, and most could be found in utterances. The data were taken from 24 students’ phatic utterances, and they were chosen because all participants are classmates. COVID-19 pandemic has forced them not to meet each other for almost 2 semesters, yet they show their closeness and solidarity. After all the data were analyzed using the qualitative method, it can be concluded that there are 7 adjacency pairs: Question-Answer, Offer-Accept, Taking leave-Taking leave, Summons-Answer, Request for information-Grant, Request-Apology, and Greeting-Greeting, and most of them have phatic functions of communication. Using adjacency pairs employs politeness strategies and negative and positive politeness strategies from Brown and Levinson. Negative politeness strategies found are Be conventionally indirect, Question, hedge, and Quality-hedges, while positive politeness strategies found are: Offer, promise, Include both S and H in the activity, and Give gifts to H. One of adjacency- pairs and phatic utterances’ functions is to maintain politeness though the students are classmates with close social distance and equal power, they perform politeness strategies to keep their social relations. The appearance of politeness strategies shows that no matter how informal utterances are, closeness and politeness must stay together.Keywords:  adjacency-pairs; phatic utterances; politeness; strategies